2007
DOI: 10.1177/039463200702000411
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Oxidative Stress and Systemic Effects in Mild Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary diseases (COPD) is a pulmonary disease characterized by systemic abnormalities. The aim of this study is to investigate inflammation and systemic effects in mild COPD. Twenty-seven mild stable smoking related COPD patients and 15 age-matched healthy subjects were enrolled in the study. IL-6, TNF-a and IL-4 in plasma, sputum and exhaled breath condensate were measured. We also measured exhaled nitric oxide (NO) and pH in sputum and in breath condensate. Moreover, fat-free mass, bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 41 publications
1
45
1
Order By: Relevance
“…Walter et al (29) showed that plasma IL-6 levels, together with age and smoking, are independent risk factors for reduced FEV1. Foschino et al (30) demonstrated that IL-6 expression levels in the airway epithelial cells of COPD patients in the acute exacerbation stage were higher compared with those in stable COPD and healthy control patients, and that IL-6 expression levels in stable COPD patients were significantly increased compared with those of healthy controls. These findings are consistent with those of the present study, with the exception that IL-6 levels in patients with stable COPD were only slightly higher compared with those in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Walter et al (29) showed that plasma IL-6 levels, together with age and smoking, are independent risk factors for reduced FEV1. Foschino et al (30) demonstrated that IL-6 expression levels in the airway epithelial cells of COPD patients in the acute exacerbation stage were higher compared with those in stable COPD and healthy control patients, and that IL-6 expression levels in stable COPD patients were significantly increased compared with those of healthy controls. These findings are consistent with those of the present study, with the exception that IL-6 levels in patients with stable COPD were only slightly higher compared with those in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, pulmonary epithelial damage is the major drawback of hyperoxia exposure [9]. AECII as the epithelial stem cell plays an important role in the maintenance of the alveolar integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, glutamate is an important precursor for the first and rate-limiting step in the synthesis of reduced glutathione, one of the most important antioxidants in muscle (5). Reduced muscle glutathione levels often result in an antioxidant/oxidant imbalance, increasing the susceptibility of the muscle to oxidative stress and cell injury (18). However, current concepts assume that oxidative stress plays a relevant role in the generation of skeletal muscle abnormalities in COPD (5).…”
Section: Rectus Femorismentioning
confidence: 99%